HOW INFLATION AFFECTS MACROECONOMIC PERFORMANCE: AN AGENT-BASED COMPUTATIONAL INVESTIGATION. (10th October 2014) - Ashraf, Quamrul; Gershman, Boris; Howitt, Peter
Abstract : We use an agent-based computational approach to show how inflation can worsen macroeconomic performance by disrupting the mechanism of exchange in a decentralized market economy. We find that, in our model economy, increasing the trend rate of inflation above 3% has a substantial deleterious effect, but lowering it below 3% has no significant macroeconomic consequences. Our finding remains qualitatively robust to changes in parameter values and to modifications to our model that partly address the Lucas critique. Finally, we contribute a novel explanation for why cross-country regressions may fail to detect a significant negative effect of trend inflation on output even when such an effect exists in reality.